Synthesis and Characterization of Some New Azo Dyes, Azomethine Dye From New Schiff Bases (2-amino fluorene/p- hydroxyacetophenone) And (2-amino fluorene/p- aminoacetophenone) (Latakia University Journal -Basic Sciences Series, 2025)
Aseries of Schiff base and their derivative (2-amino fluorene) have been synthesized by para hydroxy acetophenone was condensed with 2-amino fluorene in DMF (dimethyl form amide) in the presence of conc. HCl acid as catalyst to yield the Schiff bases (1). The Schiff’s base (1) was treated with diazotised p-sulphanilic acid to give Azo Dye compound (2), and The Schiff’s base (1) was treated with benzene diazonium salt solution to give Azo Dye compound (3), The Schiff base (4) was prepared by para amino acetophenone was condensed with 2-amino fluorene in DMF (dimethyl formamide) in the presence of conc. HCl acid as catalyst. Then the reaction of Schiff base (4) with 2-hydroxy-5-methyl-1,3-benzene dicarbox aldehyde to give Azomethine Dye compound (5).The structures of synthesized compounds has been established on the basis of their spectral (FT-IR, Mass, 1H-NMR, 13C-NMR, elemental analysis) data. TLC confirmed the purity of the compounds.